A practical guide to data analysis in general literature reviews. (December 2021) - Popenoe, Rebecca; Langius-Eklöf, Ann; Stenwall, Ewa; Jervaeus, Anna
Academic theses at the bachelor's and master's levels in nursing, physiotherapy, occupational therapy, public health and related fields often take the form of general reviews of published research on a relevant clinical issue. While there are many guides to doing literature searches and evaluating article quality, there are to our knowledge no published detailed guides of how to do the actual data analysis in such general literature reviews, particularly that are applicable to students. This article seeks to describe a systematic method of data analysis appropriate for undergraduate research theses, where the data consists of the results from available published research. We present a step-by-step guide with authentic examples and practical tips.